2021
DOI: 10.3389/fcvm.2021.714638
|View full text |Cite
|
Sign up to set email alerts
|

Early and Long-Term Follow-Up for Chronic Type B and Type Non-A Non-B Aortic Dissection Using the Frozen Elephant Trunk Technique

Abstract: Background: This study aimed to evaluate the early and long-term outcomes of a single center using a frozen elephant trunk (FET) procedure for chronic type B or non-A non-B aortic dissection.Methods: From February 2009 to December 2019, 79 patients diagnosed with chronic type B or non-A non-B aortic dissection who underwent the FET procedure were included in the present study. We analyzed operation mortality and early and long-term outcomes, including complications, survival and interventions.Results: The oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In the 7 non-comparative arch zone 2 and proximal studies, one reported both 30-day and in-hospital mortality ( 19 ), four in-hospital ( 18 , 25 , 27 , 28 ) and only two 30-day mortality ( 26 , 29 ). Here, the overall mortality rate ranged from 2.8–9.2% with an average rate of 5.4% ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 7 non-comparative arch zone 2 and proximal studies, one reported both 30-day and in-hospital mortality ( 19 ), four in-hospital ( 18 , 25 , 27 , 28 ) and only two 30-day mortality ( 26 , 29 ). Here, the overall mortality rate ranged from 2.8–9.2% with an average rate of 5.4% ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the proximal reference group, only 2 studies reported recurrent nerve palsy as outcome parameters ( 19 , 28 ). Yamamoto et al reported a rate of 0.9% ( 19 ), and Luo et al a rate of 0% ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study with a larger cohort [ 172 ] of 79 patients, the perioperative mortality, spinal ischemia and stroke rates were 5.1%, 3.8% and 2.5%, respectively. The freedom from distal interventions was 97.3%, 97.3%, 87.8%, 84.3% and 79.3% after 6 months and 1, 3, 5 and 7 years, respectively.…”
Section: Treatmentmentioning
confidence: 99%
“…The frozen elephant trunk (FET) technique is an effective surgical repair for acute and chronic aortic dissections (1)(2)(3)(4). The covering of proximal tears in the descending aorta through an FET stent-graft induces false lumen thrombosis and promotes satisfactory aortic remodeling (5).…”
Section: Introductionmentioning
confidence: 99%